2022
DOI: 10.1111/eva.13447
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the gut microbiomes and the diet of the Littorina snail ecotypes, a recently emerged marine evolutionary model

Abstract: Microbes can play a prominent role in the evolution of their hosts, facilitating adaptation to various environments and promoting ecological divergence. The Wave and Crab ecotypes of the intertidal snail Littorina saxatilis is an evolutionary model of rapid and repeated adaptation to environmental gradients. While patterns of genomic divergence of the Littorina ecotypes along the shore gradients have been extensively studied, their microbiomes have been so far over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
2
5
0
Order By: Relevance
“…Among invertebrates, mollusks stand out as ecologically significant and diverse phyla, being Gastropoda the richest class regarding species diversity (Neu et al 2019). Although descriptions of marine gastropod microbiota are accumulating, they mainly focus on commercial and/or northern hemisphere species, excluding most gastropod diversity (Neu et al 2019;Maltseva et al 2021b;Panova et al 2022). Moreover, the contribution of host diversification in shaping gastropod microbiota assembly remains largely unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…Among invertebrates, mollusks stand out as ecologically significant and diverse phyla, being Gastropoda the richest class regarding species diversity (Neu et al 2019). Although descriptions of marine gastropod microbiota are accumulating, they mainly focus on commercial and/or northern hemisphere species, excluding most gastropod diversity (Neu et al 2019;Maltseva et al 2021b;Panova et al 2022). Moreover, the contribution of host diversification in shaping gastropod microbiota assembly remains largely unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…As most organisms depend on symbioses to function, divergence in host‐symbiont relationships can be just as important to fitness as within‐species genomic divergence among ecotypes. The genomic divergence between ecotypes in Littorina was found to be mirrored by their gut bacterial community composition by Panova et al ( 2022 ). The authors found that the biofilm communities that Littorina saxatilis grazed on differed depending on habitat, which, in turn, explained gut community differences between snail ecotypes.…”
Section: Overview Of the Issuementioning
confidence: 97%
“…Library preparation and sequencing were performed as described before [35,36]. In short: genomic DNA was extracted using PowerSoil Pro Kit (QIAGEN, Hilden, Germany) according to the manufacturer's protocol.…”
Section: Library Preparation and Sequencingmentioning
confidence: 99%
“…While various trends accompanying divergence at the levels of whole genomes [34] and single genes [32] of the Littorina snails have been broadly investigated, their bacteriomes had been nearly ignored until recently. Over the past few years, general descriptions of bacterial microbiome analysis of the Littorina (Neritrema) species [35] and the ecotypes of L. saxatilis [36] were published. Moreover, a hypothesis was suggested about the role of symbionts in the reproductive barriers' formation in this group of species [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation